STRATEGI PROGRAM TVRI JAWATENGAH DALAM MENINGKATKAN KUALITAS MELALUI KONTEN BUDAYA PADA TEPOTULODHO - Ersyad, Firdaus Azwar; Murfianti, Fitri (Capture : Jurnal Seni Media Rekam, 2012)
The background of this research is based on today problems of TVRI station bothintegral and influence quality programs.The aim of the research is to know whatTVRI strategiesto upgrade the quality which has locality content function in the Tepo Tulodho programs.Thisresearch use qualitative descriptive method to dig up the empirical phenomenon in TVRI,Central Java.In addition,there are three sources: informant,document,and book.To completethe data, this research uses observation, interview, and documentation.The research resultsshowed thatTVRI used dynamic pattern in strategy program. Program production was moredominate than acquisition. Supervision and program evaluation applied by Evaluation MeetingPress. Strategy of locality culture in the TepoTulodho program described Javanese culture andone of the supporting of pictured strategy.Keywords:Program strategy, local culture, picturisation, and rtistic design.